Analisis Kualitas Website Badan Pengembangan Sumber Daya Manusia Menggunakan Metode Webqual 4.0 - Yanto Suharto; Eko Hariadi (IPB University, 2021)
This study aims to determine the quality of the website of the DKI Jakarta Province Human Resources Development Agency with the address https://www.bpsdm.jakarta.go.id as a media of information about activities and institutions related to the development of competencies for civil servants (PNS) within the Government. DKI Jakarta Province is based on the perceptions of end users by analyzing end users' perceptions of usability, informaton quality and interaction quality using the WebQual 4.0 method. Data collection was carried out by survey using a questionnaire via Geogle Form with 22 statements based on the WebQual dimension and one statement about the whole (overall) with 438 respondents from the entire population of civil servants of the DKI Jakarta Provincial Government as many as 60,691 people as of September 30, 2020, but who meet requirements as many as 398 respondents. The website quality analysis stage is by describing the survey data. The prerequisite for the test is to test the validity and reliability. Furthermore, data analysis by calculating the score and average on each indicator. The results of this test analysis indicate that the variables of usability, informaton quality and interaction quality on the website of the BPSDM DKI Jakarta Province have quality. The results of this study have implications for the need for BPSDM DKI Jakarta Province to evaluate the maintenance and development of the website that has been built used to improve service quality.